Academic Map and Hotspot Analysis of China's Legal Construction Research since the Eighteenth National Congress of the Communist Party of China: Visual Analysis Based on CiteSpace. (5th September 2022) - Peng, Hongwei
Abstract : Since the 18th National Congress of the Communist Party of China, the research on the construction of the rule of law in China has received keen attention from scholars. In this study, CSSCI literature published from 2012 to 2022 included in CNKI, Beijing Wanfang, and Chongqing VIP Chinese databases were used as data templates. NoteExpress software was used to deduplicate and organize, and 4, 603 literature related to the construction of the rule of law in China were obtained. The citespace5.8 software has carried out a visual analysis, and the results show that: (1) The research on the "rule of law China" as the overall concept in the academic circle first appeared in 2013, and the overall stability was stable, and the local volatility increased. (2) The relationship between researchers and research institutions in this field is relatively loose, and the high-yield author group has not yet been formed. (3) Through the visualization of keyword co-occurrence map and keyword clustering map and the analysis of high-frequency words and centrality, four academic maps and research hotspots are mainly proposed: core cognition of the construction of the rule of law in China, internal theory, external Practice orientation and construction path. (4) Future research on the construction of the rule of law in China strengthens the legal response to scientific and technological information, pays attention to the research on foreign-related fields of the construction of the rule of law in China, and insists on promoting the combination of "domestic rule of law" and "foreign rule of law."